Longer TA repeat but not V89L polymorphisms in the SRD5A2 gene may confer acne risk in the Chinese population - Hu, Xue; Ding, Wei; Jin, Xinye; Wang, Jia; Zou, Dajin; Chen, Yue (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Introduction : Several studies have reported that the V89L and TA repeat polymorphisms [(TA)n] of the SRD5A2 gene were associated with SRD5A2 activity. The activity of dihydrotestosterone, which is converted from testosterone by SRD5A2, is responsible for sebum secretion and the formation of acne. We hypothesized that abnormalities in SRD5A2 action could contribute to the formation of acne. Aim : To study whether the structural change of the SRD5A2 gene may affect the risk of acne in patients with normal serum testosterone levels. Material and methods : Genotyping of rs523349 and (TA)n of SRD5A2 was performed in 49 Chinese acne patients with significant improvements with SRD5A2 inhibitor-finasteride but normal serum testosterone levels, and in 50 healthy Chinese age-matched controls without acne. Results : There was no significant difference between the two groups in the frequencies of V and L alleles and VV, VL, and LL genotypes of V89L (χ 2 test, p > 0.5). (TA)n polymorphic repeat sites are 5 alleles (TA0, TA3, TA6, TA9, TA12) in our population. The differences in S and L allele frequencies between the two groups were statistically significant (p < 0.005). People with a longer (n ≥ 6) allele of the (TA)n repeat polymorphism had a higher risk of having acne than those with a shorter (n < 6) allele (OR = 3.52, 95% CI: 1.73–7.16). Conclusions : This study suggests that SRD5A2 polymorphisms might be associated with acne risk. This is the first report focusing on the Chinese population according to our knowledge. Further large sample studies may be required to confirm the association and to assess any interactions with environmental factors.